2009
DOI: 10.2108/zsj.26.301
|View full text |Cite
|
Sign up to set email alerts
|

Wing Geometric Morphometric Inferences on Species Delimitation and Intraspecific Divergent Units in theMerodon ruficornisGroup (Diptera, Syrphidae) from the Balkan Peninsula

Abstract: A study of the Merodon taxa on the Balkan Peninsula, a region with a number of Pleistocene refugia, provides a useful framework for examining evolutionary processes and detecting hidden biodiversity. The phenotypic diversity of 22 samples of the Merodon ruficornis group on the Balkan Peninsula was examined using landmark-based geometric morphometrics. The boundaries of the species M. ruficornis, M. trebevicensis, M. auripes, M. armipes, and M. Ioewi were well defined based on wing shape and size. Canonical var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 25 publications
0
18
0
3
Order By: Relevance
“…However, integrating the information from these three character systems allowed for recognition of each taxon by at least two of the data sources, and Milankov et al (2008) noted that morphological traits and COI sequences clearly separated M. armipes from M. auripes , while allozyme data did not allow diagnosis, with other examples of converse cases. Additionally, a recent study by Francuski et al (2009) using landmark‐based geometric morphometrics for the wings of the same ruficornis group species on the Balkan Peninsula, showed that wing size and shape exhibited interspecific differentiation between nearly all compared species pairs and sexes, but was not completely diagnostic for all comparisons. The above‐mentioned results greatly support a more general conclusion that species delimitation is most informative when based on an integrative approach considering several character sources, but that none of the character sources succeed in being 100% conclusive despite specimen sampling included only one particular region while several of the taxa exhibit much wider distributional ranges.…”
Section: Discussionmentioning
confidence: 99%
“…However, integrating the information from these three character systems allowed for recognition of each taxon by at least two of the data sources, and Milankov et al (2008) noted that morphological traits and COI sequences clearly separated M. armipes from M. auripes , while allozyme data did not allow diagnosis, with other examples of converse cases. Additionally, a recent study by Francuski et al (2009) using landmark‐based geometric morphometrics for the wings of the same ruficornis group species on the Balkan Peninsula, showed that wing size and shape exhibited interspecific differentiation between nearly all compared species pairs and sexes, but was not completely diagnostic for all comparisons. The above‐mentioned results greatly support a more general conclusion that species delimitation is most informative when based on an integrative approach considering several character sources, but that none of the character sources succeed in being 100% conclusive despite specimen sampling included only one particular region while several of the taxa exhibit much wider distributional ranges.…”
Section: Discussionmentioning
confidence: 99%
“…nov. Insect wing shape is highly heritable and constitutes an important character for separating species (Birdsall et al 2000). Geometric morphometric analysis of the wing shape has been successfully used in taxonomic studies of multiple hoverfly taxa (Francuski et al 2009;Vujić et al 2013b;Nedeljković et al 2013Nedeljković et al , 2015. The structure and/or shape of parts of the male genitalia are very informative and thus useful for Syrphidae taxonomy and systematics (e.g., Hippa & Ståhls 2005).…”
Section: Introductionmentioning
confidence: 99%
“…According to this, wing shape is the more important character for separating species (Birdsall et al ., ). Wing morphology has been successfully used to resolve taxonomic uncertainties within closely related species in the Syrphidae (Francuski et al ., 2009a, ; Vujić et al ., ), the Drosophilidae (Moraes et al ., ), and other insect groups, e.g. Hymenoptera (Baracchi, Dapporto & Turillazzi, ).…”
Section: Introductionmentioning
confidence: 99%